The Auditor's Role in Enhancing Financial Report Quality: An Applied Study on Iraqi Banks - Bushra Hamid Hassan AL-isami; Mondher Fakhfakh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Financial reports are vital for investment and financial decision-making, as they reflect a company's financial performance and provide key insights for investors and institutions. However, challenges such as accounting errors, financial manipulation, and non-compliance with accounting standards can impact the quality of financial reports (QFR). Auditors play a crucial role in ensuring QFR by examining and verifying financial statements, enhancing investor confidence, financial stability, and economic growth. This study examines the role of auditors in improving QFR in commercial banks listed on the Iraq Stock Exchange. Using a descriptive analytical approach, the research reviews prior studies and analyzes data from 15 commercial banks operating in the Iraq Stock Exchange from 2015 to 2021. Hypotheses were tested using Eviews-12 software. Findings indicate that auditors influence QFR through corporate governance, particularly via the board of directors, which plays a crucial role in ensuring sound auditing practices. Board independence and management ownership significantly reduce financial manipulation, aiding informed investment decisions. The study recommends increasing awareness of the auditor’s role, strengthening corporate governance mechanisms, and enhancing financial analysts' and auditors' effectiveness in reporting and forecasting. Training and development programs are also suggested to improve financial report quality in commercial banks.